The Role Of Strategic Analysis In Implementing The Frugal Innovation Strategy In The Syrian Industrial Organizations (A Case Study: Joud Industries – Domestic Appliances Company - سليطين سوما (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this research is to show the role of strategic analysis in implementing The Frugal Innovation Strategy in one of the Syrian industrial organizations, which is Joud Industries – Domestic Appliances Company. The research relied the analytical descriptive approach as a general method As For data Collection by way of questionnaire The most important results of the research have been represented as follows: 1-There is a big role of applying the strategic analysis process in The Frugal Innovation Strategy, The largest role was the process of strategic analysis of the Internal environment 2-Innovation in the company is generally characterized as Frugal Innovation even though the advantages of its products are numerous The most important recommendations are the followings : 1- The company must diversify its products by providing limited advantages products that fit Syrian limited income consumer 2-Jood Company must persevere its way in analyzing the environment and strive to improve this process, and that the most important thing it must do are the followings: - Analyzing its organizational culture, - The Use of effective methods that studies confirmed their importance in the strategic analysis process, such as the Delphi Method and The Brain Storming Method.